Decompensated chagasic heart failure versus non-chagasic heart failure at a tertiary care hospital: Clinical characteristics and outcomes - Santos,Luiza Nauane Borges Azevedo dos (2017)
Summary Objective: To evaluate clinical and epidemiological characteristics and clinical outcomes in patients hospitalized with decompensated heart failure (DHF), with a comparison between Chagas and non-Chagas disease. Method: This is a retrospective cohort study involving 136 patients consecutively admitted with DHF between January 1 and December 31, 2011, with the following outcomes: acute renal failure, cardiogenic shock, rehospitalization, and hospital death. Individuals aged ≥ 18 years with DHF were included while those with more than 10% of missing data regarding outcomes were excluded. Statistical analysis was performed using SPSS version 17.0. Chi-squared test was used to compare proportions. Student's T test was used to compare means. Kaplan-Meier and log-rank tests were used to compare rehospitalization rates between the two groups over time. Results: Chagasic and non-chagasic patients were compared. The first had lower mean systolic blood pressure (111.8±18.4 versus 128.8±24.4, p<0.01), lower mean diastolic blood pressure (74.5±13.6 versus 82.0±15.2, p<0.01) and lower left ventricular ejection fraction (26.5±6.2 versus 41.5±18.9, p<0.01). In all, 20 patients with Chagas (50.1%) were rehospitalized, compared to 35 patients in the non-Chagas group (35.4%, p=0.04). Log rank test = 4.5 (p<0.01) showed that rehospitalization rates between the two groups over time (Kaplan-Meier curves) differed. Conclusion: Chagas disease was associated with lower systolic and diastolic blood pressure and lower left ventricular ejection fraction. The rehospitalization rate was higher in Chagas disease.